A Unified Strength Model of Asphalt Mixture Considering Temperature Effect - Qian, Guoping; Yang, Hui; Li, Xi; Yu, Huanan; Gong, Xiangbing; Zhou, Hongyu (Frontiers in Materials, 2021)
The strength characteristics of asphalt mixture is crucial for the design and construction of asphalt roads. A strength model considering the effect of temperature is presented in this paper based on unified strength theory (UST). Firstly, direct tensile tests, uniaxial compression tests and anti-shear property tests of asphalt mixture were carried out respectively at different temperatures. Key mechanical parameters were obtained, including tensile strength (σt), compressive strength (σc) and shear strength (τ0) at different temperatures. Besides, the temperature sensitivity of σt, σc and τ0 was systematically analyzed. The results showed that the UST parameters of tensile-compression strength ratio α and failure criterion parameter b have a linear relationship with temperature t. A theoretical model to describe strength characteristics with the temperature of asphalt mixture was developed finally. The developed model was validated via applicability analysis. and it will provide theoretical support for the study of strength characteristics of asphalt mixture and engineering practice.